THE PRINCIPLES OF THE PROCEDURE OF HUMAN ORGAN TRANSPLANTATION - Lazic, Miroslav R (Zbornik radova Pravnog fakulteta u Nišu, 2020)
The principles of the procedure of human organ transplantation must meet two requirements: the requirement of humanity, on which medical activities are based and the requirement for the protection of patients and the preservation of human and personal rights of every man - during his life and after death. In Serbian law, the following principles are established as fundamental ones: protection of interests and dignity of donor and recipient of organ; voluntarity; medical justification and safety; equal availability of human organs. Every person having a medically established need and justification for human organ transplantation should be given equal conditions for receiving a human organ.
Keywords: трансплантација; сагласност; етика; начела